Indonesian Cinema: The Battle Over Censorship - Shadia Imanuella Pradsmadji; Nina Mutmainnah (Center for Southeast Asian Social Studies (CESASS), 2022)
The practice of film censorship has been in Indonesia since the Dutch East Indies era. Since then, film stakeholders have always been the battleground, as the different values and norms generate different views and beliefs. The critical constructionism paradigm is used to examine the contestation of film censorship in Indonesia. Four films released after the enactment of the 2009 Film Law are used as the case study: The Act of Killing, The Look of Silence, Naura & Genk Juara, and Memories of My Body. Data collection was done through a collection of news reports and social media posts that discussed the four films used as the case study. In addition, interviews with four stakeholders were done, which were an alternative cinema manager, a representative of the Indonesian Censorship Board (LSF), a representative of the Indonesian Film Body (BPI), and a film actor/director. The research results indicated that different stakeholders have different views and interests regarding film censorship, which explains why the polemic of contestation over the film censorship policy happens. Some people believe that film censorship should exist, as it would give control over society. At the same time, some people believe that film censorship should be replaced by film classification as a form of freedom of expression. There are also arguments over the standards of film censorship. Academically, the research’s significance is to develop studies regarding film censorship polemic and its stakeholders’ contestation. In contrast, practically, the research may be used to formulate film censorship regulation and policy by evaluating factors that may cause conflict among film stakeholders.